A study on portfolio diversification in Malaysian stock market - Mohamed, Zulkifli; Basri, Basaruddin Shah (Institut Penyelidikan, Pembangunan dan Pengkomersilan, 2007)
A well diversified portfolio is believed able to minimize the uncertainty of future investment's return, therefore unit trust has become new attraction to retail investors. Through diversification portfolio investment will be channeled to various stocks in share market. But the problem arises is how many stocks are required to make a well-diversified portfolio? Too many stocks will lead to high transaction cost and will reduce the total portfolio return, while too less stock will catch with under diversification. This study investigates what is the optimum number of stock that can help the investor to maximize the benefit of diversification in their investment. Using Markowitz (1952,1959) theory and simplified approach by Elton and Gruber (1977), a series of portfolio variance was derived to identify the ultimate diversification. 80 samples of stocks were randomly chosen from Bursa Malaysia for a period of 1999-2002. The finding is that in Malaysia share market, 13 stocks are enough to make a well-diversified portfolio. This finding is consistent with other markets in developed country.